Optimal extracorporeal cardiopulmonary resuscitation inclusion criteria for favorable neurological outcomes: a single‐center retrospective analysis - Otani, Takayuki (Acute Med Surg, 2019)
AIM: Although age ≤75 years, witnessed arrest, shockable initial cardiac rhythm, and short cardiac arrest duration are commonly cited inclusion criteria for extracorporeal cardiopulmonary resuscitation (ECPR), these criteria are not well‐established, and ECPR outcomes remain poor. We aimed to evaluate whether the aforementioned inclusion criteria are appropriate for ECPR, and estimate the improvements in prognoses associated with their fulfillment. METHODS: Between October 2009 and December 2017, we retrospectively examined consecutive out‐of‐hospital cardiac arrest patients who were admitted to our hospital and received ECPR. We established four ECPR inclusion criteria: age ≤75 years, witnessed arrest, shockable initial cardiac rhythm, and call‐to‐hospital arrival time ≤45 min, and also evaluated the relationship between these criteria and patient outcomes. RESULTS: During the study period, 1,677 out‐of‐hospital cardiac arrest patients were admitted to our hospital, and 156 (9%) with ECPR were examined. The proportion of favorable neurological outcomes was 15% (24/156). However, when the study population was limited to individuals who fulfilled all four criteria, 27% (15/55) had favorable neurological outcomes; only one patient had favorable outcomes when two or more criteria were fulfilled. There was a significant positive linear correlation between the proportion of cases with favorable neurological outcomes and fulfillment of the four criteria (P = 0.005, r = 0.975). CONCLUSION: Fulfillment of at least three of the aforementioned criteria could yield improved ECPR outcomes.